Global value chains participation and CO2 emissions in RCEP countries - Qian, Zhiling; Zhao, Yuhuan; Shi, Qiaoling; Zheng, Lu; Wang, Song; Zhu, Jingzhi (Journal of cleaner production, 2022)
Regional Comprehensive Economic Partnership (RCEP) is becoming the largest free trade agreement with nearly half of world's CO2 emissions. As its members are also important participants in global value chains (GVCs), studying the impact of GVCs participation on CO2 emissions in RCEP countries is of great significance. This study first calculates country level and industry level GVCs participation and CO2 emissions of 12 RCEP countries during 2000–2017. Second, impact of GVCs on CO2 emissions through scale, structure and technology effects are studied. Third, spatial spillover effects of country-level GVCs participation on CO2 emissions are studied. Fourth, impact of GVCs participation on CO2 emissions in different types of manufacture and services industries are explored. The results show that: (1) At country level, increase in GVCs forward participation reduces CO2 emissions, increase in backward participation increases CO2 emissions. (2) GVCs forward participation reduces emissions by improving production technology, backward participation increases emissions by increasing trade scale. (3) GVCs forward participation reduces emissions in home and neighbor countries, backward participation increases emissions in home countries. (4) At industry level, of all industries, increase in GVCs forward participation in medium-high tech manufacturing and productive services industries reduces more CO2 emissions than other types of industries. Increase in GVCs backward participation in low-tech manufacturing industries increases more CO2 emissions among all types of industries. •Three GVCs indicators: GVCs forward, backward participation and position are used.•Impact of forward participation is achieved through improved production technology.•Impact of backward participation is achieved through scale and technology effects.•Scale, structure, and technology effects moderate spatial spillover effect.•Higher technology industries can reduce more emissions through forward participation.